2018
DOI: 10.1007/s12195-018-0545-8
|View full text |Cite|
|
Sign up to set email alerts
|

Synergy of Paracrine Signaling During Early-Stage Mouse Ovarian Follicle Development In Vitro

Abstract: Introduction-Paracrine signals, such as soluble cytokines and extracellular matrix cues, are essential for the survival and development of multicellular ovarian follicles. While it is well established that hydrogel-based culture systems successfully support the growth of late-stage follicles for fertility preservation, growing small, early-stage ovarian follicles still proves to be challenging. We hypothesized that paracrine factors secreted from neighboring follicles may be crucial for improving the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…They grew at different rates, reaching a mean diameter of 212.36 ± 10.04 and 300.02 ± 8.00 µm (mean ± SEM) respectively (Fig. 1 B, D), corroborating previous findings 11 , 21 . There were no statistical differences in follicle survival rate between 5 and 10X conditions (Fig.…”
Section: Resultssupporting
confidence: 91%
“…They grew at different rates, reaching a mean diameter of 212.36 ± 10.04 and 300.02 ± 8.00 µm (mean ± SEM) respectively (Fig. 1 B, D), corroborating previous findings 11 , 21 . There were no statistical differences in follicle survival rate between 5 and 10X conditions (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, the 3D CM profile shows consistent concentrations of these factors over time, which corresponds to clustering of all time points in the second quadrant of the scores plot. These factors have important roles in regulating folliculogenesis 13,40 and promoting angiogenesis 41,42 , and therefore association of these factors with the co-culture and 2D CM points may account for slightly increased growth in these conditions.…”
Section: Cytokine Analysismentioning
confidence: 99%
“…Alternatively, follicles co-cultured with ovarian stromal cells had improved folliculogenesis outcomes, possibly the result of bidirectional crosstalk between the follicles and stromal cells 11 . Follicles co-cultured in groups of five or ten also show improved follicle growth outcomes over follicles cultured individually in a number dependent manner 12 stressing the importance of crosstalk between follicles and changes in the secretome 13 . These studies suggest that depending on the type of feeder cells and the paracrine mediators they secrete, unidirectional or bidirectional communication may be effective in promoting folliculogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports of the use of mesenchymal stem cells for the paracrine mediated, restoration of ovarian function in animal models of primary ovarian insufficiency [ 39 41 ] provide the basis for our hypothesis that the paracrine signals from ADSCs can rescue individually cultured primary and early secondary ovarian follicles and promote folliculogenesis [ 38 ]. We recently analyzed the secretome of human ADSCs cultured in three-dimensional culture and found statistically significant increases in cytokine production [ 36 ] and gene expression [ 38 ] among genes and cytokines that have previously been established as vital to follicular survival, growth, and development. Upregulated genes included vascular endothelial growth factor A (VEGFA), transforming growth factor-beta 2 (TGF-β2), and hepatocyte growth factor (HGF), which are known to be beneficial for follicular angiogenesis, follicular regulation, and apoptotic suppression, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulated genes included vascular endothelial growth factor A (VEGFA), transforming growth factor-beta 2 (TGF-β2), and hepatocyte growth factor (HGF), which are known to be beneficial for follicular angiogenesis, follicular regulation, and apoptotic suppression, respectively. Zhou et al demonstrated an increase in monocyte chemotactic protein-1 (MCP-1) (related to oocyte maturation), Follistatin (regulation of granulosa cell proliferation), and IL-6 (regulator of cumulus cell function) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%